Studi Eksperimen Pengaruh Variasi Besaran Sudut Buang Dan Sudut Bebas Menggunakan Pahat Tepi Rata Dengan Material Pahat HSS Terhadap Kekasaran Permukaan Pada Proses Pembubutan Benda Kerja Dengan Material Benda Kerja St 41 - Patriadicka, Gerry; Iskak, Erwansyah; -, Juanda (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2021)
A good level of surface roughness as one of the benchmarks for turning the workpiece is said to be of high quality. As a cutting tool, lathe chisels need free angles and exhaust angles according to the desired specifications. This study aims to determine the effect of variations in the size of the tool angle and how much free angle and exhaust angle are best used on the surface roughness of St 41 steel. The study was conducted using a lathe brand Bemato series 44376 with process parameters consisting of a spindle speed of 280 m /min, the infeed depth is 0.8 mm, and the infeed speed is 0.040 mm/rev. The research method used is an experimental method and the results of the turning process are measured the level of surface roughness using a surface roughness tester. Based on the results of the specimen measurements, it is found that there are differences in surface roughness produced by variations in the free angle (α) and exhaust angle (β). As for the lowest roughness value of the whole specimen turning process is in the turning process with variations in angle 6° and angle sudut 10° with a surface roughness value (Ra) of 2,555 m.